Novel approaches to the monitoring of computer networks - Halse, G A (Rhodes University, Faculty of Science, Department of Computer Science, 2003)
Traditional network monitoring techniques suffer from a number of limitations. They are usually designed to solve the most general case, and as a result often fall short of expectation. This project sets out to provide the network administrator with a set of alternative tools to solve specific, but common, problems. It uses the network at Rhodes University as a case study and addresses a number of issues that arise on this network. Four problematic areas are identified within this network: the automatic determination of network topology and layout, the tracking of network growth, the determination of the physical and logical locations of hosts on the network, and the need for intelligent fault reporting systems. These areas are chosen because other network monitoring techniques have failed to adequately address these problems, and because they present problems that are common across a large number of networks. Each area is examined separately and a solution is sought for each of the problems identified. As a result, a set of tools is developed to solve these problems using a number of novel network monitoring techniques. These tools are designed to be as portable as possible so as not to limit their use to the case study network. Their use within Rhodes, as well as their applicability to other situations is discussed. In all cases, any limitations and shortfalls in the approaches that were employed are examined.
Keywords: Computer networks; Computer networks -- Management; Computer networks -- South Africa -- Grahamstown; Rhodes University -- Information Technology Division